'Fogging' resulting in normal MRI 3 weeks after ischaemic stroke. (9th June 2011) - Choi, Philip; Srikanth, Velandai; Phan, Thanh
Abstract : CT of the brain is often negative in acute stroke. The absence of changes suggestive of infarction on MRI of the brain in the setting of a recent stroke is unusual. An otherwise fit and well 69-year-old Caucasian man presented to the hospital with a 26-h history of acute mild right hemiparesis. CT brain on arrival showed no abnormality. MRI brain was also normal 3 weeks post stroke with abnormality seen only at 11 weeks. Stroke remains a clinical diagnosis. The time of the stroke must be taken into consideration when interpreting MRI brain images. Infarct may be 'invisible' on MRI in the subacute phase of ischaemic stroke.